Coal in Turkey: Income and Price Elasticity of Coal Demand In Electricity Generation - Tatli, Halim; Barak, DoÄŸan (International Journal of Economics, Management and Accounting, 2018)
The aim of this study was to determine income and price elasticity of demand of coal used in electricity generation in Turkey. Coal demand for electricity generation was analyzed for short- and long-term effects using the ARDL bounds test. Both short- and long-term increases in coal prices reduced coal demand, while increases in per capita income increased coal demand. However, in the long-term, the effect of average temperature on coal demand was insignificant. The price elasticity of coal demand is estimated at less than 1 in both the short- (in a lagged period) and long-term. On the contrary, the income elasticity of coal demand is found larger than 1 in both the short- and long-term. In addition, firms that supply steam coal can increase their income through price increases. Therefore, it can be said that the increase in the price of coal used in electricity generation has no effect on reducing the demand for coal in this field.